Influence of distribution of zakat, Infaq And Shadaqah (ZIS), inflation and human capital on economic growth in Indonesia 2002-2021 - Suhendar, Megayana Indritia; Setyowat, Eni; Rosyadi, Imron (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Economic growth is one of the standards used to be able to see the success of economic development in a country. Indonesia, as a developing country, is actively carrying out development in a planned and gradual manner, without neglecting efforts for equity and stability. National development seeks to achieve high economic growth. Which in the end allows the realization of an increase in the standard of living and welfare of all people. In other words, a country that experiences high economic growth will be able to have a high effect on other fields, because when a country experiences economic growth, the national income of a country will be boosted up so that it can be allocated for financing economic infrastructure development. This study aims to determine the effect of zakat, infaq and shadaqah (ZIS), inflation and human capital on economic growth. This study uses time series data through data obtained at BPS from 2002-2021 as many as 20 samples with multiple linear regression method with SPSS. The results show that simultaneously zakat, infaq and shadaqah (ZIS), inflation and human capital have an effect on economic growth. Partially zakat, infaq and shadaqah (ZIS) and human capital have an effect on economic growth. Meanwhile, inflation has no effect on economic growth.